3-D Printed Directional Couplers in Circular Waveguide - Liu, W.; Chen, Z.; Viola, T.; Huff, G. H. (IEEE microwave and wireless components letters, 2021)
The design of an additively manufactured circular waveguide 3-dB hybrid directional coupler is proposed and demonstrated. Asymmetric corner radius perturbations at the in-plane orthogonal junction of the four waveguides along with curvilinear inductive posts designed to interact with the TE 11 mode of the circular waveguide are used to facilitate directivity and isolation. Capacitive waveguide perturbations at each of the four ports provide impedance matching. The proposed design is engineered to operate within V -band from 57 to 64 GHz and provide both 10-dB isolation and return loss and a 90° phase difference between the direct and coupled ports. A commercially available stereolithography (SLA) printer is used to fabricate the hybrid coupler as well as the rectangular-to-circular tapered mode transducers and the thru, reflect, line (TRL) calibration components required for experiments. The printed couplers are metallized using an electroless silver plating process by a closed-loop bidirectional multiport pump-driven fluidic system. Results from the experiment and the simulation are provided.